Manifestation of parental perfectionism on career indecision. - Khasmohammadi, Mahdi; Mohd. Noah, Sidek; Abdul Kadir, Rusnani; Baba, Maznah; Bakhash, Kiomars Farah; Keshavarz, Hossein (Elsevier, 2010)

(untitled)
The roles of family and parental perfectionism in career development are not yet understood and it has not been examined exclusively, particularly when assessing family influences in areas of career decision making and career indecision. The purpose of this study was to investigate the contribution and role of parental perfectionism to the prediction of career indecision. A sample of 102 students (32 men, 70 women) responded to Career Decision Scale and The Almost Perfect Scale-Family. Data analysis using Pearson correlation coefficient revealed that parental perfectionism did relate to the career indecision of university students. The results from the current study further expand on the results from other studies in this area by providing insight into the effects of specific family dynamics and highlight the importance of integrating parental perfectionism into the conceptualization of career development in research and practice.